The Protection of Human Rights Under the Artificial Intelligence Act - Thi Minh, Pham Trang (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
Artificial intelligence (AI) has developed rapidly and is having a profound impact on society as a whole. AI-driven technologies are now present in sectors such as healthcare, agriculture, food safety, education, media, sports, and culture, where they have the potential to optimize human time and enhance work efficiency. However, the social prospects of AI are both alluring and alarming; its promises and perils are difficult to disentangle. The risks to users have become an increasing concern as AI technologies are embedded in everyday products and services. Furthermore, AI can influence human behavior in new and unexpected ways, potentially undermining human dignity. To ensure better conditions for the application and use of AI in the development of social and economic sectors—while placing human rights at the center—the European Union enacted the AI Act, which entered into force in August 2024. This is the world’s first comprehensive AI legislation, establishing a legal framework for both users and developers of AI systems in Europe. It aims to create a safe, transparent, and trustworthy environment for the deployment of AI technologies. This paper will examine AI systems and explore the current challenges related to human rights in the context of rapid AI advancement. In addition, it will analyze the provisions of the AI Act to shed light on how it addresses the protection of human rights.